2018
DOI: 10.1021/jacs.8b01868
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Copper–Silver Alloys by Additive-Controlled Electrodeposition for the Selective Electroreduction of CO2 to Ethylene and Ethanol

Abstract: Electrodeposition of CuAg alloy films from plating baths containing 3,5-diamino-1,2,4-triazole (DAT) as an inhibitor yields high surface area catalysts for the active and selective electroreduction of CO to multicarbon hydrocarbons and oxygenates. EXAFS shows the co-deposited alloy film to be homogeneously mixed. The alloy film containing 6% Ag exhibits the best CO electroreduction performance, with the Faradaic efficiency for CH and CHOH production reaching nearly 60 and 25%, respectively, at a cathode potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
537
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 696 publications
(558 citation statements)
references
References 62 publications
19
537
0
2
Order By: Relevance
“…reported a selectivity as high as 45 % at about 150 mA cm −2 , and 60 % at 300 mA cm −2 was reported by Hoang et al. but with a bimetallic catalyst of Cu−Ag rather than plain Cu . A higher selectivity of about 80 % towards C 2 H 4 has also been reported but at a relatively low current density (∼54 mA cm −2 ) …”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…reported a selectivity as high as 45 % at about 150 mA cm −2 , and 60 % at 300 mA cm −2 was reported by Hoang et al. but with a bimetallic catalyst of Cu−Ag rather than plain Cu . A higher selectivity of about 80 % towards C 2 H 4 has also been reported but at a relatively low current density (∼54 mA cm −2 ) …”
Section: Introductionmentioning
confidence: 65%
“…This results in low current densities due to the relatively low concentration of CO 2 that can be dissolved in the electrolyte (∼35 mM under ambient conditions and neutral pH) . Recently, researchers have reported moderate to high current densities (200–600 mA cm −2 ) using gas diffusion layers (GDL's) as a substrate for the catalyst, allowing CO 2 to be supplied to the catalyst in the gas phase . Catalyst coated GDLs (also known as gas diffusion electrodes – GDE's) incorporated within flow electrolyzers under alkaline conditions have shown improved performance in terms of selectivity and current densities.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…To date, vast efforts have been devoted to optimizing the electrocatalytic CO 2 RR to EtOH, mainly through tailoring the physical structures and surface compositions of the applied Cu‐based electrocatalysts . Based on these efforts, one strategy is constructing steps, edges, or grain boundaries on the electrocatalyst surface to expose under‐coordinated Cu atoms, which could act as the catalytically active sites for C 2 products formation .…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxide derived Cu films with rough appearance could generate C 2 H 4 and EtOH of Faradaic efficiency (FE) of 39% and 16%, respectively . The other strategy is introducing a cocatalyst to catalyze additional CO formation, which acts as a feedstock during the CO 2 RR; the formed CO molecules from the cocatalyst sites would couple with CH 2 * intermediate (* indicates the adsorbed species) on Cu sites to promote EtOH production . Excellent CO‐producing cocatalysts cover Au, Zn, and Ag, etc.…”
Section: Introductionmentioning
confidence: 99%